2017
DOI: 10.1002/2016jf003992
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stress weathering and the spalling of Antarctic rocks

Abstract: Using in situ field measurements, laboratory analyses, and numerical modeling, we test the potential efficacy of thermal stress weathering in the flaking of millimeter‐thick alteration rinds observed on cobbles and boulders of Ferrar Dolerite on Mullins Glacier, McMurdo Dry Valleys (MDV). In particular, we examine whether low‐magnitude stresses, arising from temperature variations over time, result in thermal fatigue weathering, yielding slow crack propagation along existing cracks and ultimate flake detachmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 90 publications
(120 reference statements)
2
43
0
1
Order By: Relevance
“…Our rock erosion framework is supported by a number of experimental and field observations, as well as by theoretical studies: Even over relatively short (Holocene) timescales, regardless of rock type or environment, the outer millimeter to centimeter thick portion of rock surfaces is characterized by chemically and physically altered weathering rinds that thicken and intensify in their accumulation of weathering products through time [ Birkeland , ; Burke and Birkeland , ; Hoke and Turcotte , ; Warke and Smith , ]. Accumulation of weathering products presumably “primes” this outer shell for wholesale exfoliation and/or susceptibility to thermal stresses, as proposed by some work [ Lamp et al , ; Tratebas et al , ]. A large majority of all subaerially exposed rocks show evidence of this type of surface parallel fracturing and/or granular disintegration regardless of environment and/or stress loading process. For example, freezing, fire, salt hydration, and thermal cycling have all been demonstrated to induce exfoliation [e.g., Al‐Omari et al , ; Turkington and Paradise , ; Vasile and Vespremeanu‐Stroe , ], and such spallation occurs in subsurface rock weathering as well [ Fletcher and Brantley , ]. Similar surface fragmentation models have been explored and validated, for example, in the context of dissolution weathering rinds [ Hoke and Turcotte , ] or salt weathering [ Wells et al , ]. …”
Section: A Simple Model Of Rock Erosion By Climate‐dependent Subcritimentioning
confidence: 99%
See 1 more Smart Citation
“…Our rock erosion framework is supported by a number of experimental and field observations, as well as by theoretical studies: Even over relatively short (Holocene) timescales, regardless of rock type or environment, the outer millimeter to centimeter thick portion of rock surfaces is characterized by chemically and physically altered weathering rinds that thicken and intensify in their accumulation of weathering products through time [ Birkeland , ; Burke and Birkeland , ; Hoke and Turcotte , ; Warke and Smith , ]. Accumulation of weathering products presumably “primes” this outer shell for wholesale exfoliation and/or susceptibility to thermal stresses, as proposed by some work [ Lamp et al , ; Tratebas et al , ]. A large majority of all subaerially exposed rocks show evidence of this type of surface parallel fracturing and/or granular disintegration regardless of environment and/or stress loading process. For example, freezing, fire, salt hydration, and thermal cycling have all been demonstrated to induce exfoliation [e.g., Al‐Omari et al , ; Turkington and Paradise , ; Vasile and Vespremeanu‐Stroe , ], and such spallation occurs in subsurface rock weathering as well [ Fletcher and Brantley , ]. Similar surface fragmentation models have been explored and validated, for example, in the context of dissolution weathering rinds [ Hoke and Turcotte , ] or salt weathering [ Wells et al , ]. …”
Section: A Simple Model Of Rock Erosion By Climate‐dependent Subcritimentioning
confidence: 99%
“…This strength is dictated by material properties such as tensile strength ( σ T ) or fracture toughness ( K c aka critical stress intensity factor), which are themselves dependent on inherent material properties like Young's modulus or Poisson's ratio. With few exceptions [e.g., Eppes et al , ; Lamp et al , ; Walder and Hallet , ], environmentally driven weathering studies in particular have almost invariably applied an equilibrium law approach, asking: Does σ process exceed σ critical ? [e.g., Al‐Omari et al , ; Bost and Pouya , ; Jiménez‐González et al , ; Ravina and Zaslavsky , ; Roering et al , ; Wang and An , ].…”
Section: Introductionmentioning
confidence: 99%
“…Field observations of thermal stress weathering on Earth have been well documented (Aldred et al, ; Collins & Stock, ; Eppes, McFadden, Wegmann, & Scuderi, ; Koch & Siegesmund, ; Lamp et al, ; Ollier, ; Rice, ; Siegesmund, Ullemeyer, Weiss, & Tschegg, ; Sumner, Hedding, & Meiklejohn, ; Viles, ; Weiss, Siegesmund, Kirchner, & Sippel, ). In particular, McFadden, Eppes, Gillespie, and Hallet (), Eppes et al (), and (Eppes et al, ) observed that most crack features in boulders lying in the deserts of Arizona, east United States, Australia, and Mongolia exhibited an N–S orientation, strong circumstantial evidence that these crack features were driven by thermal stresses induced by heating from the sun moving along an E‐W path relative to the boulder.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that these airless bodies experience large diurnal temperature variations (on the order of ∼100 K), thermal stress weathering has long been presumed to be of little significance in the inner solar system. Within the last decade, thermal stress weathering has been revisited with greater rigour and is now suspected to play an important role in rock breakdown, regolith generation, crater degradation, and landscape evolution in Earth's deserts and cold regions (Hall, ; Lamp, Marchant, Mackay, & Head, ), Mars (Eppes, Willis, Molaro, Abernathy, & Zhou, ; Viles et al, ), Mercury (Molaro & Byrne, ), Moon (Mazrouei, Ali Lagoa, Delbo, Ghent, & Wilkerson, ; Molaro, Byrne, & Langer, ; Molaro, Byrne, & Le, ; Ruesch et al, ), near‐Earth asteroids (Delbo et al, ; Dombard, Barnouin, Prockter, & Thomas, ; Graves, Minton, Molaro, & Hirabayashi, ; Jewitt, ), and perhaps comets (Alí‐Lagoa, Delbo, & Libourel, ; El‐Maarry et al, ; Pajola et al, ; Shestakova & Tambovtseva, ; Tambovtseva, Grinin, & Kozlova, ).…”
Section: Introductionmentioning
confidence: 99%
“…Bachmann et al, 2004;Huisman et al, 2011). Weathering processes operate concurrently and/or interact with a range of other processes that prepare slopes for macroscale fracture (Aldred et al, 2016;Atkinson, 1984;Collins and Stock, 2016;Eppes and Keanini, 2017b;Eppes et al, 2016;Gischig et al, 2011;Lamp et al, 2017;Rosser et al, 2013;Stock et al, 2012) but their combined effect on rock mass strength and failure style remains poorly constrained. Selby, 1980;Hoek, 1983), but such schemes do not sufficiently consider weathering-induced strength degradation of intact rock bridges that critically influence shallow rock slope failures and rockfall activity, which are our focus here (de Vilder et al, 2017;Jennings, 1970;Kemeny, 2005).…”
Section: Introductionmentioning
confidence: 99%